2013
DOI: 10.1017/thg.2012.155
|View full text |Cite
|
Sign up to set email alerts
|

Neurodevelopmental Outcome Among Multiples and Singletons: A Regional Neonatal Intensive Care Unit's Experience in Turkey

Abstract: Objective: The aim of this study was to compare the neurodevelopmental outcome at 12–18 months’ corrected age between multiples and singleton preterm infants. Methods: We designed a prospective study of preterm infants (≤32 weeks gestation) born and hospitalized in the neonatal intensive care unit between November 2008 and November 2009, whose assessments were performed at 12–18 months’ corrected age. Neurodevelopmental impairment was defined as the presence of any one of the following: moderate or severe cere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 24 publications
1
15
0
Order By: Relevance
“…In this sample of extremely preterm infants who survived to follow-up at age 10 years, we found no evidence that twins or triplets (who comprised 35% of this cohort) had worse neurocognitive outcomes than singletons born at the same gestational age. Our findings are consistent with the majority of follow-up studies that assessed children in the pre-school age period,(14, 15, 25, 26) but are in contrast to several prior population-based studies. (24, 10) Our findings suggest that the so called “cognitive cost” of being born a twin has diminished or that children born extremely preterm differ from those born at or near term.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In this sample of extremely preterm infants who survived to follow-up at age 10 years, we found no evidence that twins or triplets (who comprised 35% of this cohort) had worse neurocognitive outcomes than singletons born at the same gestational age. Our findings are consistent with the majority of follow-up studies that assessed children in the pre-school age period,(14, 15, 25, 26) but are in contrast to several prior population-based studies. (24, 10) Our findings suggest that the so called “cognitive cost” of being born a twin has diminished or that children born extremely preterm differ from those born at or near term.…”
Section: Discussionsupporting
confidence: 91%
“…Large population-based studies, dating back to the 1950’s, demonstrated a disadvantage of as much as 4 to 5 IQ points among twins, when compared to singletons. (24, 10, 13, 27) Relatively recent population-based studies from the Netherlands,(11, 28) and Turkey,(25) however, suggests that twins born at or near term perform as well academically as singletons in adolescence.…”
Section: Discussionmentioning
confidence: 99%
“…Bodeau-Livinec et al (2013) utilized the Kaufmann Assessment Battery for Children for cognitive assessment, and cerebral palsy was also assessed, while Gnanendran et al (2015) utilized the BSID and Griffiths Mental Development Scales. Hjern et al (2012) utilized test scores from the 'Enlistment Battery 80' , used for military conscription at 18-19 years of age to create an indicator of IQ and grade point averages from the national school register, while Eras et al (2013) utilized the BSID, MDI, and Psychomotor Developmental Index (PDI).…”
Section: Methodsmentioning
confidence: 99%
“… Gnanendran et al (2015) reported that multiples (<29 weeks) and similarly preterm singletons at 2–3 years of corrected age did not have significantly higher rates of neurodevelopmental impairment. Similarly, Eras et al (2013) did not find any significant association between multiple birth in preterm infants (≤32 weeks) and increased risk of neurodevelopmental deficits at 12–18 months’ corrected age.…”
Section: Discussionmentioning
confidence: 78%